2019
DOI: 10.1101/632810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Well-Differentiated Papillary Mesothelioma of the Peritoneum is Genetically Distinct from Malignant Mesothelioma

Abstract: Well-differentiated papillary mesothelioma (WDPM) is an uncommon mesothelial proliferation that is most commonly encountered as an incidental finding in the peritoneal cavity. There is controversy in the literature about whether WDPM is a neoplasm or a reactive process, and if neoplastic, whether it is a variant or precursor of epithelial malignant mesothelioma or is a different entity. Using whole exome sequencing of five WDPM of the peritoneum, we have identified distinct mutations in EHD1, ATM, FBXO10, SH2D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…At the genetic level, some researchers have studied the mutations in WDPMT. Shrestha found that EHD1, ATM, FBXO10, SH2D2A, CDH5, MAGED1, and TP73 mutations are present in WDPMT, but they are rare in malignant mesotheliomas pointing out that these mutations may be specific to WDPMT (15). Another study suggesting the presence of TRAF7 or CDC42 missense mutations in WDPMT can be used to distinguish it from mesothelioma (16).…”
Section: Discussionmentioning
confidence: 99%
“…At the genetic level, some researchers have studied the mutations in WDPMT. Shrestha found that EHD1, ATM, FBXO10, SH2D2A, CDH5, MAGED1, and TP73 mutations are present in WDPMT, but they are rare in malignant mesotheliomas pointing out that these mutations may be specific to WDPMT (15). Another study suggesting the presence of TRAF7 or CDC42 missense mutations in WDPMT can be used to distinguish it from mesothelioma (16).…”
Section: Discussionmentioning
confidence: 99%